El problema de la gestión de la inclusión de las tecnologías de la información y la comunicación en la educación rural Peruana - Espíritu Barrón, Edmundo Morello (2021)
The research work presented below will analyse whether the investment in training in ICTrelated issues influences the Educational Management and the Teaching and Learning Processes of the educational institutions of Regular Basic Education of the educational levels of primary (6 to 12 years of age) and secondary (12 to 17 years of age) belonging to six Peruvian villages of rural areas. For this purpose, various quantitative instruments were applied to teachers at three times (baseline, midterm and expost) in two school years. The population of this work was 40 teachers, all from rural areas of the Peruvian highlands and jungle (Amazonas, Cajamarca and Junín). The results show that, in the four dimensions analysed, the progress was significant through the three stages of the evaluation, which shows that the inclusion of ICT offers great opportunities for improving educational management and teaching processes learning in the institutions studied.